Mexico : Report on the Observance of Standards and Codes-Fiscal Transparency Module. (IMF Staff Country Reports; Country Report ;, 2002)
This report assesses the Observance of Standards and Codes on Fiscal Transparency Module for Mexico. In recent years, Mexico has made considerable progress in improving transparency in public finances. Major initiatives include reform of the budget process; preparation of an integrated financial management information system; phase-in of a system of human resource management; overhaul of public procurement; streamlining of government regulations; strengthening of internal control and external audit; introduction of prudential criteria for state development banks; and reduction of discretionality in intergovernmental relations.